The Iloilo maritime legacy project an integrated of a residual waste-to-liquid fuel plant, maritime museum, and public park - Carpio, Stephany Bernice S. (College of Architecture, University of the Philippines Diliman, 2019)
The Iloilo Maritime Legacy Project was devised using the agenda-based approach. This entailed choosing a macro site first, studying its context (i.e. history, development, problems, goals, etc.), deriving an agenda, and finally, identifying an appropriate project that would see it through. The macro site chosen is Iloilo City, an emerging economics center in the Philippines with a strong maritime culture that stems back to Pre-Hispanic times. Due to its rapid urbanization, a number of problems have emerged - such as waste management. After studying those problems, as well as the goals the city holds for its future, the following agenda was derived: a need for an innovative, revenue-generating, sustainable industry to promote a healthy productive Ilonggo community that would propel the city to reclaim its title of "Queen City of the South". The proponent then chose to use Iloilo City's maritime culture as the context of this venture; in order to anchor it in Iloilo's past, present and future and, thus, bring the pursuit of the title of "Queen City of the South" full circle. The feasible project identified was an integration of a maritime museum, a public park, and a residual plastic-to-liquid-fuel plant. Its mission would be to memorialize the past, recognize all who contribute to the maritime industry at present, and safeguard the industry's future. It would carry this out by teaching its visitors about the rich maritime culture of Iloilo, supplying fuel to a portion of the city's maritime vessels, while at the same time redirecting residual waste which would have ended up going to the city's landfill or polluting its waterbodies. The site-specific design problem was how to integrate the three facilities in a way that was attractive, inviting, and immersive but did not compromise the different safety and security with the pyrolysis process line to pique interest, this idea eventually had to be set aside in the visibility, accessibility, and attractiveness to the visitor while the back prioritizes privacy, security, and safety. Galleries, activity spaces, offices, and storage rooms are located in the main building up front while facilities part of the pyrolysis process were located in the back. From the exhibit focused perspective of a visitor, the plant facilities are only amongst the many attractions - as well as quite disconnected from the main visitor areas. In this way, they are thought of rather as a separate existence. However, the success of one facility is highly influenced by the success of the other, and is rooted in the importance of the role played by the site itself - its history, location, and the establishments in its immediate vicinity. These factors anchor both facilities to each other and their surroundings.